Pengaruh Potongan Harga Dan Komunikasi Bisnis Terhadap Loyalitas Pelanggan Pembelian Stick Tahu Toko Aqia Kediri - Nada Liyana Putri; Bambang Suwarsono; Brahma Wahyu Kurniawan (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
This research aims to partially and simultaneously explain the influence of price discounts and business communication on customer loyalty in purchasing Tofu Sticks at the Aqia Kediri Store. This type of research uses quantitative research. Data sources use primary data and secondary data. The sample in the research was 87 customers who purchased Toko Aqia Kediri's Tofu Stick using purposive sampling technique. The analysis techniques used are validity test, reliability test, normality test, linearity test, multicollinearity test, heteroscedasticity test, t test, F test, multiple linear regression analysis, t test, F test and coefficient of determination (R2) test using the SPSS program version 25. The results of this research are that partially the price discount variables and business communication have a positive and significant effect on customer loyalty in buying tofu sticks at the Aqia Kediri Store. Simultaneously, the variables of price discounts and business communication have a significant effect on customer loyalty in purchasing tofu sticks at the Aqia Kediri Store.